(untitled) (Communications in Computational Physics, 2020)
As a spatially extended dissipative system with strong nonlinearity, the radio-frequency (rf) dielectric-barrier discharges (DBDs) at atmospheric pressure possess complex spatiotemporal nonlinear behaviors. In this paper, the time-domain nonlinear behaviors of rf DBD in atmospheric argon are studied numerically by a one-dimensional fluid model. Simulation results show that, under appropriate controlling parameters, the rf DBD can undergo a transition from single-period state to chaos through period doubling bifurcation with increasing discharge time, i.e., the regular periodic oscillation and chaos can coexist in a long time series of the atmospheric-pressure rf DBD. With increasing applied voltage amplitude, the duration of the periodic oscillation reduces gradually and chaotic zone increases, and finally the whole discharge series becomes completely chaotic state. This is different from conventional period doubling route to chaos. Moreover, the spatial characteristics of rf period-doubling discharge and chaos, as well as the parameter range of various discharge behaviors occurring are also investigated in this paper.